Analysis of Total Iron-Binding Capacity (TIBC) in Pregnant Women in Palembang City - Swarsa, Rachma Dhini; Garini, Ardiya; Harianja, Sri Hartini (Journal of Noncommunicable Diseases Prevention and Control, 2024)
Total Iron-Binding Capacity (TIBC) is a test to determine the total iron in serum and is used as one of the clinical diagnoses of iron deficiency anemia. The TIBC levels will increase during pregnancy. This study aimed to determine the factors that are related to TIBC levels in pregnant women at the Vitri Suzanti independent midwife practice in Palembang in 2024. The type of research used was descriptive observational with a cross-sectional approach, with a total of 38 pregnant women as respondents, taken by accidental sampling. The examination material in the form of 3 mL of venous blood was taken from each respondent to then was processed into serum, and a TIBC examination was carried out at the Palembang Public Health Laboratory Center (BBLKM). Each respondent was also given a questionnaire regarding parity status, age, gestational age, iron consumption, employment status, education status, and family income level. The results of filling out the questionnaire and the respondents' TIBC levels obtained were then analyzed statistically using SPSS software version 26 by conducting a Chi-square test. The results showed that the frequency distribution of normal TIBC levels was 32 people (84.2%). The results of the Chi-square analysis showed no relationship between the TIBC levels and parity status (p=0.294), maternal age (p=1.000), gestational age (p=0.199), iron consumption (p=0.578), employment status (p=0.302), maternal education (p=1.000), and family income (p=0.682).